Temperature of Interest Enhanced Seed Germination and Early Vegetative Growth Among Cowpea Cultivars Under Heat Stress - Abiala, Moses; Srivastava, Richa; Sahoo, Lingaraj (AGRIVITA Journal of Agricultural Science, 2026)
As a result of the increase in global temperature, cowpeas have been predicted to be one of the crops to face more frequent exposures to heat stress. This study investigates the effect of heat stress on stress-tolerant cowpea cultivars (Ifebrown-IF, Danila-DN, and Alokalocal-AK) from seed germination to early vegetative growth. Cultivars were exposed to different temperature regimes (27±3°C, 37±3°C) for 40 days and nights. IF and DN cultivars had early seed germination at both temperature regimes in comparison to the AK cultivar, which had delayed germination at 27±3°C. At the early vegetative growth stage, increased proline content, reduced oxidative stress, relative leaf temperature, stomatal conductance, reduced transpiration rates, and photosynthesis rates shifted each cultivar to the temperature of interest. Both temperature regimes favored DN and AK cultivars, while only 27±3°C supported IF cultivars, with evidence in their chlorophyll content, leaf area (LA), plant height (PH), fresh-shoot weight (FSW), and dry-shoot weight (DSW) in comparison to IF cultivars that had poor growth at 37±3°C. Thus, temperatures of interest are important to ensure tolerance of specific cowpea cultivars from seed germination to early vegetative growth under heat stress.